THE EFFECT OF FINANCIAL LITERACY, INCOME AND PER-CEIVED RETURN ON INVESTMENT DECISIONS - Agustya Ningrum, Dewi; Susanti, Jenny (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2023)
This study aims to examine the influence of financial literacy, income, and return perception on investment decision-making among the people of Sidoarjo. The research method used was quantitative method with a sample of 100 respondents selected through purposive sampling technique. Data collected was through questionnaires and analyzed using statistical analysis technique, data quality testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The research results demonstrate that financial literacy, income, and return perception both partially and simultaneously have a positive and significant impact on investment decision-making among the people of Sidoarjo. This indicates that the more financially literate people are, along with stable income and positive return perception, the more likely they are to make appropriate investment decisions. This research has important implications for enhancing financial literacy and understanding the importance of income and return perception in investment decision-making. This study is expected to provide recommendations to the government and financial institutions to enhance financial literacy and improve access to investment information for the public.